A Comparison of Sprint Mechanical Parameters Measured With Timing Gates and a Laser Gun - van den Tillaar, Roland; Haugen, Markus Estifanos; Falch, Hallvard Nygaard (Frontiers in Sports and Active Living, 2022)
The aim of the study was to compare sprint mechanical parameters measured with timing gates and a laser gun. Thirty-four female team handball players (age: 17.0 ± 2.3 years, height: 1.70 ± 0.07 m, body mass: 66.7 ± 9.7 kg) performed three 30 m sprints in which the times were measured at 5, 10, 20 and 30 m with timing gates (accuracy 0.01 s) together with the distance over time by a laser gun. The main findings were that with a correction of +0.21 s (timing gates) the times and sprint mechanical properties calculated with the spreadsheet of Morin between timing gates and laser gun were not different. But when peak velocity was derived directly from the laser gun (MusclelabTM system) this was significantly higher than maximal velocity (vmax), and lower than the theoretical maximal velocity (v0) calculated with the spreadsheet. It was concluded that a correction of +0.21 s should be used to get correct mechanical properties when measuring with timing gates compared with laser gun measurements on an indoor court.